Efficacy of Essential Oil Strips Containing Thymol, Eucalyptol, Menthol, Methyl Salicylate, and Peppermint Against Dental Caries - Rahardjo, Anton; Gemiani, Dira; Soekanto, Sri A (Makara Journal of Health Research, 2018)
Background: Strips containing essential oils are commonly used as an alternative treatment for dental caries prevention. However, their efficacy is unknown. This study aimed to test the efficacy of oral strips containing essential oils on caries prevention. Methods: This was a randomized, double-blind, placebo-controlled crossover study with 15 subjects divided into two groups: A and B. In the first week, group A (N = 8) was given strips containing thymol, eucalyptol, menthol, methyl salicylate, and peppermint (TEMMP) three times in 24 hours while group B (N = 7) was given placebo strips. In the second week, after a one-week washout period, each group was given the other product. Pre- and post-treatment evaluation was performed by measuring plaque acidity using a pH plaque indicator and determining the number of S.mutans colonies using a hand counter. Results: There was no significant difference between plaque pH and S.mutans count in subjects given TEMMP strips compared to placebo. Conclusions: The use of TEMMP essential oil strips does not significantly inhibit the growth of S.mutans or the production of plaque.